Exploring the timing of medical student research internships: before or after clerkships? - van Wijk, Inge J. (BMC Med Educ, 2018)
BACKGROUND: The objective of this study was to determine the optimal positioning of the research internship, either before clinical clerkships, at the beginning of the medical Master’s programme, or at the end. METHODS: A mixed methods study was carried out. We compared characteristics such as duration, location and grades for internships performed and students’ motives for choosing to perform their research internship before or after clinical clerkships. We analysed students’ answers to open-ended questions about the reasons for their choices, using the Self-Determination Theory of motivation. RESULTS: Students performing their research internship before clinical clerkships (n = 338) opted more often for an extended internship (OR = 3.16, 95% CI = 2.32–4.31) and an international location (OR = 2.22, 95% CI = 1.46–3.36) compared to those performing their research internships after clinical clerkships (n = 459). Neither the internship grades nor the number of international publications differed significantly between the two groups. Most of the students’ motives (102 participants) were classified as extrinsic motivation for research. Students performing research before clinical clerkships more often showed intrinsic motivation for research, students performing research after clinical clerkships were mainly motivated by their career choice. CONCLUSION: To accommodate both groups of students, offering research internships before and after clinical clerkships, is recommended.